Being an Involved Father: What Does It Mean? - Kate Fogarty; Garret D. Evans (EDIS)
Revised! FCS2141, a 5-page fact sheet by Kate Fogarty and Garret D. Evans, explores the meaning of “involvement” for fathers, and provides some strategies for having healthy and involved relationships with one’s children. Includes references. Published by the UF Department of Family, Youth and Community Sciences, November 2009.